2003
DOI: 10.1046/j.1351-0754.2003.0565.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of arbuscular mycorrhizal colonization and environment on root development in soil

Abstract: Summary The production of fine roots is one of the principal means by which carbon, fixed during photosynthesis, enters the soil, and quantifying the production for particular combinations of environmental and biotic factors is important for predicting the sequestration of carbon in the soils of grassland ecosystems. Arbuscular mycorrhizal fungi (AMF) can have a major effect on the production of roots, and we studied how colonization by AMF affects the lifespan of roots. Twenty per cent of control roots of Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…The anatomical, physiological, and morphological characteristics within the fi ne root architecture differ with species (Bouma et al 2001a, b;Comas et al 2002;Pregitzer et al 2002), nutrient concentration (Cruz et al 2004;Pregitzer et al 2002), soil layer (Bauhus and Messier 1998;Fujimaki et al 2004;Godbold et al 2003;Hishi et al 2006;Leuschner et al 2004), and soil organism communities (Atkinson et al 2003;Hooker et al 1992;Wells et al 2002). The great plasticity of fi ne roots in response to the environment suggests that mortality and decomposition of individual roots may change, mediated by changes in the allocation of biomass to individual roots with different functions or demographic traits within the fi ne root architecture.…”
Section: Heterogeneity In Decomposition Rates Within the Fi Ne Root Amentioning
confidence: 96%
See 1 more Smart Citation
“…The anatomical, physiological, and morphological characteristics within the fi ne root architecture differ with species (Bouma et al 2001a, b;Comas et al 2002;Pregitzer et al 2002), nutrient concentration (Cruz et al 2004;Pregitzer et al 2002), soil layer (Bauhus and Messier 1998;Fujimaki et al 2004;Godbold et al 2003;Hishi et al 2006;Leuschner et al 2004), and soil organism communities (Atkinson et al 2003;Hooker et al 1992;Wells et al 2002). The great plasticity of fi ne roots in response to the environment suggests that mortality and decomposition of individual roots may change, mediated by changes in the allocation of biomass to individual roots with different functions or demographic traits within the fi ne root architecture.…”
Section: Heterogeneity In Decomposition Rates Within the Fi Ne Root Amentioning
confidence: 96%
“…Fungal biomass on individual roots is higher on thin (<0.5 mm in diameter) short roots than on long thin roots and thick (0.5-1.0 mm in diameter) roots in Japanese red pine (Satomura et al 2003). Several studies have reported that colonization by arbuscular mycorrhizae changes fi ne root morphology (Hooker et al 1992) depending on temperature or nutrient conditions (Atkinson et al 2003), although some studies have reported that the effect of nutrients on root morphology was stronger than that of infection of arbuscular mycorrhizae (Cruz et al 2004).…”
Section: Heterogeneity In Morphological Characteristics Of Individualmentioning
confidence: 98%
“…These alterations of root morphological traits were greatest when inoculated with P. occultum, greater with G. mosseae and least with G. versiforme. Indeed, growth and development of plant roots are strongly affected by mycorrhizal fungi (Hodge et al 2009) and root traits, such as total length, tap length, diameter, branching, volume, surface area and number were altered by AMF colonization (Schellenbaum et al 1991;Hooker et al 1992;Atkinson et al 2003;Gutjahr et al 2009;Yao et al 2009;Orfanoudakis et al 2010). Our results in these root traits of trifoliate orange (Table 2) are consistent with those in grapevine, beach plum and red tangerine (Augín et al 2004;Zai et al 2007;Wu et al 2010) and might indicate that the magnitude of root morphological alteration could be dependent on AMF species.…”
Section: Plant Growth and Root Morphologymentioning
confidence: 99%
“…Furthermore, root development is a highly plastic process which is influenced by plant endogenous characteristics (genetic control) and different external stimuli (environmental control) (Malamy 2005), and it is well known that P availability could act as an external signal with a profound impact on root system development (López-Bucio et al 2003). Also, there is evidence that AM fungi could substantially change root architecture (Atkinson et al 2003).…”
mentioning
confidence: 99%